Bangladeshi parents’ knowledge and awareness about cervical cancer and willingness to vaccinate female family members against human papilloma virus: a cross sectional study - Sultana, Anjuman; Jahan Shimu, Shakila; Jakanta Faika, M.; Islam, Thrina; Ferdous, Noor-E-; Nessa, Ashrafun (International Journal Of Community Medicine And Public Health, 2023)
Background: Cervical cancer (CC) is an important cause of cancer death among Bangladeshi women and human papillomavirus (HPV) is the causative factor for developing CC. HPV vaccination is yet to be implemented as part of national immunization programme in Bangladesh. Method: The objective of this cross-sectional research was to evaluate the understanding of CC, HPV, and the willingness to accept HPV vaccination among parents of school-aged children (between 5-16 years) from grades 1-10 in the capital city of Bangladesh, Dhaka. The study was conducted from February 2020 to January 2021 by paper-based survey. Results: This study showed 86.6% of participants knew that CC is preventable and 98.6% knew that vaccine can prevent CC. Only 1.3% of the participants heard about HPV. Majority (97.1%) were interested in HPV vaccination to female family members. Knowledge about visual inspection with acetic acid (VIA) test, CC prevention and HPV vaccine were significantly associated with willingness to give vaccine. Gender, age, educational level and socioeconomic condition of respondents have no relation with vaccine acceptance (p>0.05). This study showed that total 1319 (45%) respondents sought the vaccine free of cost and personal relation as friends and family were major source of information (64.8%). Conclusions: The study’s results revealed that a significant number of Bangladeshi parents were aware of CC, CC prevention, and HPV vaccination. Nonetheless, most participants expressed a willingness to vaccinate their female family members against HPV.